Woman suffrage by federal constitutional amendment (National suffrage library, 1917)
This collection of essays focuses on the various arguments for and against woman suffrage by federal constitutional amendment rather than by individual states. An essay by Henry Wade Rogers provides an interesting counterpoint to another volume in this collection, "Woman's Suffrage by Constitutional Amendment," by Henry St. George Tucker [Section VII, no. 380].